Illuminating Information Creating: Using the "Four C" Model of Creativity as a Lens for ILS - Thompson, Leslie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2018)
Information creating is understudied in the ILS field. This paper introduces the interdisciplinary “Four C” Model of Creativity (Kaufman & Beghetto, 2009) and begins to employ it as a lens for conceptualizing and approaching information-creating research. The “Four C” model distinguishes four main types or modes of creativity. When translated into ILS, the model serves as a platform for aggregating information-creating research, synthesizing across it, recognizing gaps in it, and growing this research area overall.